Identification of novel pathways and immune profiles related to sarcopenia - Abdelrahman, Zeinab; Wang, Xiaosheng; Wang, Daming; Zhang, Tianfang; Zhang, Yue; Wang, Xuhua; Chen, Zuobing (Frontiers in Medicine, 2023)
Sarcopenia is a progressive deterioration of skeletal muscle mass strength, and function. To uncover the underlying cellular and biological mechanisms, we studied the association between sarcopenia’s three stages and the patient’s ethnicity, identified a gene regulatory network based on motif enrichment in the upregulated gene set of sarcopenia, and compared the immunological landscape among sarcopenia stages. We found that sarcopenia (S) was associated with GnRH, neurotrophin, Rap1, Ras, and p53 signaling pathways. Low muscle mass (LMM ) patients showed activated pathways of VEGF signaling, B cell receptor signaling, ErbB signaling, and T cell receptor signaling. Low muscle mass and physical performance (LMM_LP) patients showed lower enrichment scores in B cell receptor signaling, apoptosis, HIF-1 signaling, and the adaptive immune response pathways. Five common genes among DEGs and the elastic net regression model, TTC39DP, SLURP1, LCE1C, PTCD2P1, and OR7E109P, are expressed between S patients and healthy controls. SLURP1 and LCE1C showed the highest expression levels among sarcopenic Chinese descent than Caucasians and Afro-Caribbeans. Gene regulatory analysis of top upregulated genes in S patients yields a top-scoring regulon containing GATA1, GATA2, and GATA3 as master regulators and 9 predicted direct target genes. Two genes were associated with locomotion: POSTN and SLURP1. TTC39DP upregulation was associated with a better prognosis and stronger immune profile in S patients. The upregulation of SLURP1 and LCE1C was associated with a worse prognosis and weaker immune profile. This study provides new insight into sarcopenia’s cellular and immunological prospects and evaluates the age and sarcopenia-related modifications of skeletal muscle.